Creating Resilient Landscapes in an Era of Climate Change Global Case Studies and Real-World Solutions - Jarchow, Meghann; Rastandeh, Amin (2022)
This book delivers a realistic and feasible framework for creating resilient landscapes in an era of anthropogenic climate change.From across six continents, this book presents fifteen case studies of differing sociocultural, economic, and biophysical backgrounds that showcase opportunities and limitations for creating resilient landscapes throughout the world. The potential to create socio-ecological resilience is examined across a wide range of landscapes, including agricultural, island, forest, coastal, and urban landscapes, across sixteen countries: Argentina, Australia, Brazil, Denmark, Finland, Greece, Guatemala, Japan, Mexico, Norway, Samoa, South Africa, the United States, Turkey, Uruguay, and Vanuatu. Chapters discuss current and future issues around creating a sustainable food system, conserving biodiversity, and climate change adaptation and resilience, with green infrastructure, nature-based architecture, green-tech, and ecosystem services as just a few of the approaches discussed. The book emphasizes solution-oriented approaches for an "ecological hope" that can support landscape resiliency in this chaotic era, and the chapters consider the importance of envisioning an unpredictable future with numerous uncertainties. In this context, the key focus is on how we all can tackle the intertwined impacts of climate change, biodiversity loss, and large-scale land-cover conversion in urban and non-urban landscapes, with particular attention to the concept of landscape resiliency. The volume provides that much-needed link between theory and practice to deliver forward-thinking, practical solutions.This book will be of great interest to students, researchers, practitioners and policymakers who are interested in the complex relationship between landscapes, climate change, biodiversity loss, and land-based conversion at local, national and global scales.